Patients with both CYP2C19 loss-of-function allele and peripheral endothelial dysfunction are significantly correlated with adverse cardiovascular events following coronary stent implantation. Issue 1 (January 2016) - Tabata, Noriaki; Hokimoto, Seiji; Akasaka, Tomonori; Arima, Yuichiro; Sakamoto, Kenji; Yamamoto, Eiichiro; Tsujita, Kenichi; Izumiya, Yasuhiro; Yamamuro, Megumi; Kojima, Sunao; Kaikita, Koichi; Kumagae, Naoki; et al.
Abstract: Background: There is some controversy regarding the effect of CYP2C19 polymorphism on clinical outcome in patients receiving dual antiplatelet therapy (DAPT). Peripheral endothelial dysfunction has recently been reported to predict adverse cardiovascular events. We hypothesized that CYP2C19 loss-of-function (LOF) allele carriers with peripheral endothelial dysfunction had worse prognosis. The aim of this study was to evaluate an additive effect of peripheral endothelial dysfunction on clinical outcome following percutaneous coronary intervention (PCI) in patients with a CYP2C19 variant. Methods: We enrolled 434 patients on DAPT following PCI. CYP2C19 genotype was examined, and we divided patients into two groups: carriers, who had at least one CYP2C19 LOF allele, and non-carriers. Peripheral endothelial dysfunction was examined using reactive hyperemia-peripheral arterial tonometry index (RHI), and we divided patients into low and high RHI. Thus, subjects were divided into four groups, and clinical events were followed up. Results: A total of 55 patients had a cardiovascular event. Kaplan–Meier analysis demonstrated a significantly higher probability of cardiovascular events in carriers with low RHI (log-rank test: p  = 0.007). Multivariate Cox proportional hazards analysis identified both CYP2C19 LOF allele possession (hazard ratio (HR): 1.94; 95% confidence interval (CI): 1.1–3.69; p  = 0.045) and low RHI (HR: 2.15; 95% CI: 1.22–3.78; p  = 0.008) as independent and significant predictors of future cardiovascular events. Conclusions: CYP2C19 LOF allele carriers with peripheral endothelial dysfunction were significantly correlated with cardiovascular events. The additional evaluation of peripheral endothelial function along with CYP2C19 polymorphism might improve risk stratification after coronary stent implantation.